Предмет: Математика, автор: hamrae

решить линейное уравнение
4х-2(2-х²)=х²+5х-(3-х²)

Ответы

Автор ответа: sebrithien
2

Ответ:

x  =  - 1

Пошаговое объяснение:

4x - 2(2 -  {x}^{2} ) =  {x}^{2}  + 5x - (3 -  {x}^{2} ) \\ 4x - 4 + 2 {x}^{2}  =  {x}^{2}  + 5x - 3 +  {x}^{2}  \\ 2 {x}^{2}  -  {x}^{2}  -  {x}^{2}  + 4x - 5x =  - 3 + 4 \\  - x = 1 \\ x =  - 1

Автор ответа: YasminaKhiz2007
0

Ответ:4x-2(2-x²)=x²+5x-(3-x²)

4x-4+2x²=x²+5x-3+x²

4x+2x²-x²-5x-x²=(-3)+4

4x-5x=1

-x=1

x=1÷(-1)

x=-1

Похожие вопросы
Предмет: Алгебра, автор: bibikvera942